(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Diabetes mellitus (DM) is a metabolic disorder resulting from a defect in insulin secretion, and it has been described as a public health challenge of the 21st century. A survey was carried out in Gashua metropolis Yobe State Northeas Nigeria between August, 2021 and February, 2022, to ascertain the prevalence of Diabetes mellitus (DM) among the residents. Out of One hundred (100) blood samples that were collected from age group 15-60 years and analysed in the Haematology unit, Yobe State Specialist Hospital Gashua, prevalence rate of 14(14. 0)% was observed . The gender of study population was also considered where more positive samples were observed among females than their male counterparts. The higher prevalence of Diabetes mellitus recorded could be attributed to increase in individual-level risk factors. There is a need for strategic planning towards change in lifestyle amongst in order to reduce the devastating effects of the disease.